2015
DOI: 10.1002/lno.10157
|View full text |Cite
|
Sign up to set email alerts
|

The role of ecophysiological and behavioral traits in structuring the zooplankton assemblage in a deep, oligotrophic, tropical lake

Abstract: Zooplankton inhabiting deep, oligotrophic, tropical lakes must cope with scenarios where the combination of resource limitation, high visual‐predation risk, UV‐induced damage and seasonal development of anoxic waters, entail particular challenges for organisms, uncommon in temperate environments. We assessed the diel vertical migration—DVM—(UV/predation‐avoidance strategy), numerical response, and starvation resistance (physiological strategies to cope with food scarcity) of the copepod Leptodiaptomus garciai … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The copepod L . garciai is the main component of the zooplankton assemblage; in a previous paper we concluded that it is present throughout the year despite the often-limiting availability of phytoplankton, owing to its low food threshold (C 0 ) and high resistance to starvation; in addition, it performs diel vertical migrations to avoid light-related mortality factors (UV damage and/or predation risk) [ 27 ]. There are also two rotifer species ( Brachionus sp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The copepod L . garciai is the main component of the zooplankton assemblage; in a previous paper we concluded that it is present throughout the year despite the often-limiting availability of phytoplankton, owing to its low food threshold (C 0 ) and high resistance to starvation; in addition, it performs diel vertical migrations to avoid light-related mortality factors (UV damage and/or predation risk) [ 27 ]. There are also two rotifer species ( Brachionus sp.…”
Section: Methodsmentioning
confidence: 99%
“…As we intend to describe the environmental conditions experienced by copepods at a given day, we took into account that adult individuals of L . garciai perform diel vertical migrations–moving across a vertical gradient of biotic and abiotic conditions- and avoid the anoxic hypolimnion during the summer stratification of the lake [ 27 ]. In addition, we assumed they also evade the surface of the water column as has been observed in crustacean zooplankton inhabiting other highly transparent lakes [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, until recently, the influence of phytoplankton diversity on the stability of zooplankton and the underlying mechanisms remained unclear. In addition, both phytoplankton and zooplankton are complex in taxonomic composition, and these groups have their own ecophysiological traits [18,37]. It remains unknown whether the temporal stability of these plankton taxa responds similarly to variations in diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Lake Alchichica investigations have included both general limnology and all trophic levels (cf., Macek et al, 2009;Oliva et al, 2001;Ciros-Pérez et al, 2015, for bacteria, phytoplankton and zooplankton / fish interactions, respectively). Subtropical lakes Biwa (Japan) and Kinneret (Israel) have also been well studied (Madoni, 1990;Hu and Kusuoka, 2015).…”
Section: Introductionmentioning
confidence: 99%